Educators in non-formal vocational education and training in Mozambique: a plea for recognition and professionalisation. Issue 3 (4th May 2017) - Manuel, Alzira; van der Linden, Josje; Popov, Oleg
Abstract: Interest in vocational education and training (VET) is growing. This can be attributed to global socio-economic developments requiring continuously changing knowledge and skills. Adult education and training, particularly in non-formal education (NFE) contributes to provide these skills and knowledge for youth and adults. This puts pressure not only on programmes and facilities, but also on the educators. How do they cope with the changing demands? This paper focuses on educators in non-formal vocational education and training (NFVET) in Mozambique. It explores the perceptions, experiences and reflections of educators in NFVET working in training centres on the outskirts of Maputo. Semi-structured interviews and observations were used to get insight into the educators' understandings and into the conditions in which their educational activities took place. The findings point to the need for the professionalisation of NFVET educators. This would contribute to the quality of their activities and to their status as professionals.